2018
DOI: 10.3390/ijerph15091847
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risks in Vitiligo Patients: A Nationwide Population-Based Study in Taiwan

Abstract: Vitiligo is an autoimmune disease characterized by destruction of melanocytes and associated with other autoimmune disease. Whether the dysregulation of immune system enhances oncogenesis or not remains obscure. Until now, no nationwide population-based study has been conducted regarding this. As such, this paper aims to clarify cancer risk in vitiligo patients. A retrospective nationwide population-based cohort study between 2000 and 2010 was performed based on data from the National Health Insurance Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…Later, the patient was diagnosed with gastric carcinoma, and surgery was performed [11]. Although vitiligo predominates in a large number of people, it is not yet confirmed that the coexistence of vitiligo and tumors are merely a coincidence or whether they have a common biological explanation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Later, the patient was diagnosed with gastric carcinoma, and surgery was performed [11]. Although vitiligo predominates in a large number of people, it is not yet confirmed that the coexistence of vitiligo and tumors are merely a coincidence or whether they have a common biological explanation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the mortality risk in psoriasis patients with respect to disease severity [8,10,11,26,27,28]. Among these studies, four suggested an increased mortality in both patients with mild and severe psoriasis compared with the general population [8,10,27,28]; one reported a significant higher risk of mortality in patients with severe psoriasis [11].…”
Section: Discussionmentioning
confidence: 99%
“…The NHIRD database contains registration files and original reimbursement claims data, including demographic characteristics, outpatient and inpatient services, diagnostic codes, procedures performed, and details of prescriptions and comorbidities. The NHIRD has been widely used in epidemiological studies [19,20,21,22,23,24,25,26]. Previous studies have confirmed the high accuracy and validity of the NHIRD in recording psoriasis [10].…”
Section: Methodsmentioning
confidence: 99%
“…Two other studies have been conducted in Asia, and they provide conflicting results. Harrist et al .…”
mentioning
confidence: 97%
“…report no skin cancer outcomes in either vitiligo or nonvitiligo groups in India. The Taiwanese study by Cheng‐Yan et al . (the only other population‐based study ever conducted) showed a decreased risk of NMSC and an increased risk of melanoma in patients but was limited by statistical power.…”
mentioning
confidence: 99%